DETECTING FRAUD FINANCIAL STATEMENTS IN MANUFACTURING COMPANIES INDONESIA - Budiandru Budiandru; Zakkiandri Zakkiandri; Basyiruddin Nur; Yeni Elfiza Abbas; Ilza Febrina (Fakultas Ekonomi Universitas IBA, 2022)
The purpose of this research is toand analyze the influence of the four elements infraud triangle that is pressure, opportunity, and rationalization. to detect the possibility of fraudulent financial statements (financial statement fraud). The four elements will be divided into 5 variables, specifically financial stability,external pressure, ineffective monitoring, nature of industry, and change in auditors.to find the possibility of fraudulent financial statements as measured by the M Score modelin manufacturing companiesin the 2018-2021 period. The results of the study show that of the six variables used in the study, there is one (1) variable, namely the nature of the industry which has a significant effect on the possibility of fraudulent financial statements. While the other five (5) variables financial targets, external pressure, ineffective monitoring, and auditor changes do not affect the likelihood of fraudulent accounts. The contribution of the results of this our riset that manufacturing companies in that year are likely to be more concerned or careful the nature of industry that has a significant impact, this will affect the sustainability of the business in the future.